A novel MALDI-TOF MS-based method for blood meal identification in insect vectors: A proof of concept study on phlebotomine sand flies - Hlavackova, Kristyna; Dvorak, Vit; Chaskopoulou, Alexandra; Volf, Petr; Halada, Petr (PLoS neglected tropical diseases, 2019)
BACKGROUND: Identification of blood sources of hematophagous arthropods is crucial for understanding the transmission cycles of vector-borne diseases. Many different approaches towards host determination were proposed, including precipitin test, ELISA, DNA- and mass spectrometry-based methods; yet all face certain complications and limitations, mostly related to blood degradation. This study presents a novel method for blood meal identification, peptide mass mapping (PMM) analysis of host-specific hemoglobin peptides using MALDI-TOF mass spectrometry. METHODOLOGY/PRINCIPAL FINDINGS: To identify blood meal source, proteins from abdomens of engorged sand fly females were extracted, cleaved by trypsin and peptide fragments of host hemoglobin were sequenced using MALDI-TOF MS. The method provided correct host identification of 100% experimentally fed sand flies until 36h post blood meal (PBM) and for 80% samples even 48h PBM. In females fed on two hosts, both blood meal sources were correctly assigned for 60% of specimens until 36h PBM. In a validation study on field-collected females, the method yielded unambiguous host determination for 96% of specimens. The suitability of PMM-based MALDI-TOF MS was proven experimentally also on lab-reared Culex mosquitoes. CONCLUSIONS/SIGNIFICANCE: PMM-based MALDI-TOF MS analysis targeting host specific hemoglobin peptides represents a sensitive and cost-effective method with a fast and simple preparation protocol. As demonstrated here on phlebotomine sand flies and mosquitoes, it allows reliable and rapid blood source determination even 48h PBM with minimal material input and provides more robust and specific results than other currently used methods. This approach was also successfully tested on field-caught engorged females and proved to be a promising useful tool for large-scale screening of host preferences studies. Unlike other methods including MALDI-TOF protein profiling, it allows correct identification of mixed blood meals as was demonstrated on both experimentally fed and field-collected sand flies.
Keywords: Psychodidae; Hemoglobins; druhová specificita; stravovací zvyklosti; Blood Chemical Analysis; tandemová hmotnostní spektrometrie; ověření koncepční studie; hemoglobiny; Species Specificity; Proof of Concept Study; Animals; lidé; Humans; zvířata; Peptides; spektrometrie hmotnostní - ionizace laserem za účasti matrice; peptidy; Tandem Mass Spectrometry; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; biochemická analýza krve; Feeding Behavior